Effect of Boric Acid Content in Aluminosilicate Matrix on Mechanical Properties of Carbon Prepreg Composites - Haincová, Eliška; Hájková, Pavlína (Materials (Basel, Switzerland), 2020)
This work presents carbon fabric reinforced aluminosilicate matrix composites with content of boric acid, where boron replaces aluminum ions in the matrix and can increase the mechanical properties of composites. Five different amounts of boric acid were added to the alkaline activator for preparing six types (including alkaline activator without boric acid) of composites by the prepreg method. The influence of boric acid content in the matrix on the tensile strength, Young's modulus and interlaminar strength of composites was studied. Attention was also paid to the influence of boron content on the behavior of the matrix and on the internal structure of composites, which was monitored using a scanning electron microscope. The advantage of the aluminosilicate matrix is its resistance to high temperatures; therefore, tests were also performed on samples affected by temperatures of 400-800 °C. The interlaminar strength obtained by short-beam test were measured on samples exposed to 500 °C either hot (i.e. measured at 500 °C) or cooled down to room temperature. The results showed that the addition of boron to the aluminosilicate matrix of the prepared composites did not have any significant effect on their mechanical properties. The presence of boron affected the brittleness and swelling of the matrix and the differences in mechanical properties were evident in samples exposed to temperatures above 500 °C. All six prepared composites showed tensile strength higher than 320 MPa at laboratory temperature. The boron-free composite had the highest strength 385 MPa. All samples showed a tensile strength higher than 230 MPa at elevated temperatures up to 500 °C.
Keywords: composite; temperature resistant; carbon fiber; short-beam; prepreg; tensile strength